The spatial-temporal risk profiling of Clonorchis sinensis infection over 50 years implies the effectiveness of control programs in South Korea: a geostatistical modeling studyResearch in context - Hai-Yan Xiao; Jong-Yil Chai; Yue-Yi Fang; Ying-Si Lai (The Lancet Regional Health. Western Pacific, 2023)
Summary: Background: Over the past 50 years, two national control programs on Clonorchis sinensis infection have been conducted in South Korea. Spatial-temporal profiles of infection risk provide useful information on assessing the effectiveness of the programs and planning spatial-targeted control strategies. Methods: Advanced Bayesian geostatistical joint models with spatial-temporal random effects were developed to analyze disease data collecting by a systematic review with potential influencing factors, and to handle issues of preferential sampling and data heterogeneities. Changes of the infection risk were analyzed. Findings: We presented the first spatial-temporal risk maps of C. sinensis infection at 5 × 5 km2 resolution from 1970 to 2020 in South Korea. Moderate-to-high risk areas were shrunk, but temporal variances were shown in different areas. The population-adjusted estimated prevalence across the country was 5.99% (95% BCI: 5.09–7.01%) in 1970, when the first national deworming campaign began. It declined to 3.95% (95% BCI: 2.88–3.95%) in 1995, when the campaign suspended, and increased to 4.73% (95% BCI: 4.00–5.42%) in 2004, just before the Clonorchiasis Eradication Program (CEP). The population-adjusted prevalence was estimated at 2.77% (95% BCI: 1.67–4.34%) in 2020, 15 years after CEP started, corresponding to 1.42 (95% BCI: 0.85–2.23) million infected people. Interpretation: The first nationwide campaign and the CEP showed effectiveness on control of C. sinensis infection. Moderate-to-high risk areas identified by risk maps should be prioritized for control and intervention. Funding: The National Natural Science Foundation of China (project no. 82073665) and the Natural Science Foundation of Guangdong Province (project no. 2022A1515010042).